Clostridial Gas Gangrene ‐ A Rare but Deadly Infection: Case series and Comparison to Other Necrotizing Soft Tissue Infections - Leiblein, Maximilian (Orthop Surg, 2020)
OBJECTIVE: Clostridial gas gangrene (GG) or clostridial myonecrosis is a very rare but life‐threatening necrotizing soft tissue infection (NSTI) caused by anaerobic, spore‐forming, and gas‐producing clostridium subspecies. It is the most rapidly spreading and lethal infection in humans, also affecting muscle tissue. The high mortality, of up to 100%, in clostridial GG is mediated by potent bacterial exotoxins. Necrotizing fasciitis (NF) is an important differential diagnosis, most often caused by group A streptococci, primarily not affecting musculature but the subcutaneous tissue and fascia. In the early stages of the infection, it is difficult to distinguish between GG and NF. Therefore, we compare both infection types, identify relevant differences in initial clinical presentation and later course, and present the results of our patients in a retrospective review. METHODS: Patients diagnosed with GG from 2008 to 2018 in our level one trauma center were identified. Their charts were reviewed retrospectively and data analyzed in terms of demographic information, microbiological and histological results, therapeutic course, outcome, and mortality rates. The laboratory risk indicator for NF (LRINEC) score was applied on the first blood work acquired. Results were compared to those of a second group diagnosed with NF. RESULTS: Five patients with GG and nine patients with NF were included in the present study. Patients with GG had a mortality rate of 80% compared to 0% in patients with NF. In eight patients with NF, affected limbs could be salvaged; one NF underwent amputation. LRINEC did not show significant differences between the groups; however, C‐reactive protein was significantly increased (P = 0.009) and hemoglobin (Hb) was significantly decreased (P = 0.02) in patients with GG. Interleukin‐6 and procalcitonin levels did not show significant difference. Patients with GG were older (70.2 vs 50 years). Of the isolated bacteria, 86% were sensitive to the initial calculated antibiotic treatment with ampicillin‐sulbactam or imipenem plus metronidazole plus clindamycin. CONCLUSION: Both GG and NF need full‐scale surgical, antibiotic, and intensive care treatment, especially within the first days. Among patients with NSTI, those with clostridial GG have a significantly increased mortality risk due to early septic shock caused by clostridial toxins. In the initial stages, clinical differences are hardly detectable. Immediate surgical debridement is the key to successful therapy for NSTI and needs to be performed as early as possible. However, patients should be treated in a center with an experienced interdisciplinary intensive care team based on a predetermined treatment plan.